The Word Reference and the Rhetorical Styleverses 23 and 24 of Esraa Sura as Model - Ezzat, Azza Adnan Ahmed (Arab Journal for Sciences and Research Publishing, 2019)
Shedding light on ayas of the Quranic text is still a rich resource for various linguistic studies, and it will be constantly providing us with information up to the end of the world. Suppose that each letter in the Glorious Quran hasn't been stated randomly but fit and exactly; even the word and the style haven't indefinitely been mentioned in vain.We have tried to show an aspect of miraculous linguistic expression in the Quranic text throughout tackling two ayas which are at least regarded as a basic core of community construction; since they arrange the relationship among parents and sons within the family, in addition to the relationship of a worshiper towards his/her worshiped (i.e. the Almighty Allah), and its involved influence on the humans treatment with each other. On this basis, it can be said that “the religion is the life”.In this regard, it has been dealt with the word: its sounds, its meanings, its aspect, the manner of its writing, and its position within the structure. Starting with the phonetic rhythmic aspect related to vowel sounds, it has been shown the rising and falling  of vowel sounds rate in an amazing harmony with the topic and theme of the aya. The vowel sound alif (الألف) in the first aya has got about 90% and this is in harmony with the topic of monotheism and the fate of the Almighty Allah.On the other side, the ratio of the vowel sound yaa' (الياء) is decreasingly amounted as 25% in the second aya; in a way that is in harmony with the meaning of the aya, since it talks about lowering the wing of humiliation and mercy (i.e. to treat them mercifully and pray for them to get the merci of Allah for their binging up and taking care the sons when they were little).It has been shown the semantic perspective of these sounds and the phonetic syllables within the words with their inflectional cases, in addition to the harmony of type of definition in such sounds and the type of the used pronoun. Accordingly, it has been found that the strong meanings are coherent with strong sounds in the used utterances compared with their synonyms. As for the grammatical structure, however, the scenes have been symbolized throughout the images gotten by the lexicons such as (the wing of humiliation and mercy) which draws the image of humiliation and submission. The mark of (kasra) at the end of the lexicon (الرحمةِ) is in harmony with the treating case, and this is in harmony with the use of antecedent pronoun (referring to the addressor) in the lexicon (ربّياني) instead of (ربّياكَ). According to phonetic properties, the increasing of sound figures in the word draws an increasing careand mercy, in addition to the denotation of   the vowel sound yaa' (الياء) by which the word (ربّياني) is ended. It is indefinitely softer than the sound letter kaf (الكاف) w.
Keywords: Harmony; consonance; meaning; vowels; consonants; syllable